2016
DOI: 10.7314/apjcp.2016.17.4.1925
|View full text |Cite
|
Sign up to set email alerts
|

Variant Alleles in XRCC1 Arg194Trp and Arg399Gln Polymorphisms Increase Risk of Gastrointestinal Cancer in Sabah, North Borneo

Abstract: Background: The XRCC1 protein facilitates various DNA repair pathways; single-nucleotide polymorphisms (SNPs) in this gene are associated with a risk of gastrointestinal cancer (GIC) with inconsistent results, but no data have been previously reported for the Sabah, North Borneo, population. We accordingly investigated the XRCC1 Arg194Trp and Arg399Gln SNPs in terms of GIC risk in Sabah. Materials and Methods: We performed genotyping for both SNPs for 250 GIC patients and 572 healthy volunteers using a polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In agreement with our results, Halim et al [14] reported that the 194Trp allele is significantly associated with high risk for the development of CRC. The frequency of the 194Trp allele in our study was similar to that previously reported in studies from Egypt and Mexico [15,16].…”
Section: Discussionsupporting
confidence: 83%
“…In agreement with our results, Halim et al [14] reported that the 194Trp allele is significantly associated with high risk for the development of CRC. The frequency of the 194Trp allele in our study was similar to that previously reported in studies from Egypt and Mexico [15,16].…”
Section: Discussionsupporting
confidence: 83%
“…The outcomes of some investigation about the association of XRCC1 (rs25487) polymorphism with colorectal cancer risk have been contradictory. For example, two recent studies indicated association with increased risk of colorectal cancer (Karam et al, 2016;Abu Halim et al, 2016), while a case-control study in Sweden found no association with CRC risk (Salimzadeh et al, 2020). Also, other findings about the association of OGG1 (rs1052133) polymorphism with susceptibility to CRC remain controversial (Lai et al, 2016;Zou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The 399Gln allele frequency was found higher when compared to Egyptian, Han Chinese, Japanese, Korean and Western Mexican populations but was lower than in the Thai population gastrointestinal cancer population. (Halim et al, 2016) Rajadurai (2017) has found human epidermal growth factor receptor2 (HER2) overexpression, a biomarker of breast cancer, in advanced GCa and gastroesophageal junction cancer. HER2 overexpression was evident in nearly 24.6% (56/288) of the Malaysian,and significantly more among males and diffuse-type tumors.…”
Section: Histologymentioning
confidence: 99%